Laboratory analysis of rubber wastes in order to their utilization in energy sector - Budzyń, Stanisław; Jakóbiec, Janusz; Tora, Barbara; Żmuda, Wiesław Andrzej (My University, 2013)
W artykule przedstawiono wyniki badania produktów pirolizy granulatu z odpadów gumowych (opon). Proces pirolizy był prowadzony w temperaturze 450, 500, 550 i 600 stopni Celsjusza. Określono uzyski produktów pirolizy (karbonizat, olej i gaz). Określono właściwości fizykochemiczne produktów oraz skład chemiczny popiołu po ich spaleniu. Przedstawiono możliwości wykorzystania produktów pirolizy.

This paper presents the results of the pyrolysis process of waste rubber — tire granulate. The process was carried out over four temperatures: 450, 500, 550 and 600 degrees of Celsius. The yield of post pyrolysis products (carbonizate, oil and gas) was specified. Physicochemical properties of char, oil and gas, chemical composition of ash after burning was also determined. The possibilities of the carbonizate were also shown.
Badania laboratoryjne pirolizy odpadów gumowych pod kątem ich wykorzystania energetycznego
AGH Journal of Mining and Geoengineering
Keywords: rubber wastes; odpady gumowe; calorific value; energia; energy; piroliza; pyrolysis; kaloryczność